Establishing Depression Levels among Women Seeking Obstetric Fistula Treatment at Fistula CarePlus Supported Sites in Uganda (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims:This paper reports on the magnitude of depression among women with Obstetric Fistula.Methods: Between June 2016 and December 2017, 10 nurses and midwives at four hospitals in Uganda (Hoima, Kamuli, Kitovu, and Jinja) were trained to evaluate depression among obstetric fistula clients using the PHQ-9 tool. The tool was scored at admission and at two weeks after surgery. Psychotherapy was provided after surgery. Depression severity was categorized from mild to severe and frequencies were tabulated. Scores from before and after treatment were compared in a subset of clients from Kamuli.Results:Obstetric Fistula clients (180) were assessed preoperatively for depression at Hoima (55), Kamuli (59), Kitovu (22), and Jinja (44). All clients at Hoima (15.2% mild, 24.5% moderate, 28.3% moderate to severe and 32% severe) and Kamuli (23.7% mild, 13.6% moderate, 27.1% moderate to severe and 35.6% severe) had depression before treatment and pyschotherapy. At Kitovu and Jinja depression levels were 81% (13.6% Minimal, 4.5% moderate, 36.4% moderately severe, 45.5% severe) and 84% (Mild 36.5%, Moderate -36.5%, Moderate to Severe-9.7%, severe depression-17.3%) respectively. Post treatment screening was conducted at Kamuli and all clients still had depression but of less severity (Mild -94.9%, Moderate -3.4%%, Moderate to Severe 1.7%, severe depression - 0).Conclusions:Clients with obstetric fistula have high levels of depression. Psychotherapy and surgery can mitigate depression symptoms.Keywords: depression, fistula, psychotherapy, surgery